2020
DOI: 10.3389/fpubh.2019.00410
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Occupational Stress on Job Burnout Among Bank Employees in Pakistan, With Psychological Capital as a Mediator

Abstract: Background: Job burnout is a major issue for workers in the banking sector. Many employees report feeling exhausted and want to leave their jobs due to the extra pressure and workload from their superiors and clients. They also report not being well compensated for their hard work, which they believe they do to provide the best service to their clients. Methods: A cross-sectional study was made in various banks in different cities of Pakistan. An adapted questionnaire, including the effort-reward imbalance sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 39 publications
2
40
0
1
Order By: Relevance
“…As indicated above, several studies documented that psychological capital is related to life satisfaction [ 34 , 36 , 43 ] and positive wellbeing [ 34 , 39 , 40 , 41 , 42 , 44 ], not to mention many positive work-related outcomes [ 27 , 33 , 46 , 47 , 48 , 49 ]. This research also demonstrated strong positive associations between satisfaction with life and PsyCap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated above, several studies documented that psychological capital is related to life satisfaction [ 34 , 36 , 43 ] and positive wellbeing [ 34 , 39 , 40 , 41 , 42 , 44 ], not to mention many positive work-related outcomes [ 27 , 33 , 46 , 47 , 48 , 49 ]. This research also demonstrated strong positive associations between satisfaction with life and PsyCap.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, research has documented associations between psychological capital and several wellbeing outcomes, including health [ 37 , 38 , 39 , 40 , 41 , 42 ], life satisfaction [ 36 , 43 ], quality of life [ 44 ], employment [ 27 ], academic performance [ 45 ], not to mention many positive work-related outcomes [ 33 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the performance of Chinese commercial banks and the quality of service delivered by front-line employees become extremely important. Khalid et al (2020) stated that employees in the Pakistan banking sector face pressure from both their supervisors and clients. This would bring a negative influence on the quality of service delivery and burnout experience among front-line employees in the banking sector.…”
Section: Problem Statementmentioning
confidence: 99%
“…Moreover, psychological well-being concentrates on the positive emotion presence of the employees during a stable time period, which means front-line employees in Chinese commercial banks with a high level of psychological well-being are more likely to deliver high-quality customer service. Previous studies by Khalid et al (2020), Khattak et al (2011) and Bashir (2010) focus on the negative job outcomes of employees in banking sector such as job stress and burnout. However, this study aims to extend the focus on the positive job attitude and positive well-being of employees, which are job satisfaction and psychological well-being.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…It is also considered a real mental health threat as it is a main cause of Burn-Out (BO) especially in the healthcare sector [9]. In fact, the risk of burnout in areas of high occupational stress is seven times greater than that in areas of low occupational stress [10].…”
Section: Introductionmentioning
confidence: 99%